Handling of Theft Cases Based on Restorative Justice at the Muara Enim District Attorney’s Office - Syalwa Putri Khairumi; Faisal Abdaud; Huzaiman Huzaiman (LEGAL BRIEF, 2026)
This study investigates the implementation of restorative justice in addressing theft cases during the prosecution phase at the Muara Enim District Attorney’s Office, reflecting a paradigm shift in the Indonesian criminal justice system from a retributive model to one focused on social repair. The study aims to examine the implementation mechanisms, challenges faced, and the efficacy of restorative justice in addressing minor criminal cases and reducing recidivism. The employed method is an empirical legal approach utilizing a field-based methodology that includes interviews, observations, and an examination of legal documents pertaining to law enforcement officers and applicable legislation. The research results indicate that restorative justice has been actively and effectively applied in resolving cases through the discontinuation of prosecution, reconciliation between victims and suspects, and follow-up rehabilitation programs in the form of social sanctions, skills training, and community supervision. Nevertheless, its implementation still faces challenges such as limited budgets, time, and facilities, as well as social and emotional factors among the parties involved. Thus, restorative justice has proven to be a more humane, efficient, and recovery-oriented legal solution, although it still requires institutional strengthening and broader social support.